Gain coefficient and resonator losses of neodymium- doped yttrium aluminium garnet laser - Abdul Hadi, Norha (2009)
The resonator losses and gain coefficient in the laser material are very important in the optimization process of a laser system especially in Q-switching. The purpose of this study is to determine the gain coefficient and resonator losses of Nd:YAG laser system and also to determine the maximum output energy at different mirror reflectivity. The Findlay-Clay analysis is an easy method to characterize the resonator losses and gain coefficient by using output mirrors with different reflectivities, R. In this study, xenon flashlamp was used as a pumping source for Nd:YAG laser crystal. The laser chamber was deposed in a plano-concave resonator. The Nd:YAG laser system was operated only for single pulse in two mode, free running and Q-switch. The output energy of the laser was verified by using seven different reflectivity output coupler. The result obtained showed that, the resonator losses and gain coefficient of threshold energy for free running mode operation are 1.128 and 0.075 and for Qswitch mode operation are 0.171 and 0.011 . This study expected that the energy losses should be greater in Q-switched mode because the absorption and reflection in the beam modulator as well as the effect of electro-optic.